ASSESSMENT OF REPRODUCTIVE HEALTH AWARENESS AMONG ADOLESCENT GIRLS IN A CITY OF SOUTH INDIA: AN INTERVENTIONAL STUDY. - Josephine Priya K; Ranganath T Sobagaiah; Ipsita Debata (Universitas Ahmad Dahlan, 2022)
Background: An adolescent in the age group of 10 – 19 years is subjected to the vicious cycle of early marriage, early and repeated pregnancies, poor nutrition and ill health. Betterment can only occur by educating them and promoting health awareness and healthy behavior among them. A study to identify the lacunae in awareness levels among this demographic and measures to overcome the same through targeted education is the need of the hour.Objectives: The objectives of this study are to assess the existing Reproductive Health awareness among adolescent girls and to evaluate the change in awareness levels after educational intervention.Methods: An educational interventional study was carried out in high schools and pre university colleges in a city in south India. A total of 800 students from Class VIII to XII from 6 educational institutions were studied using a standardized, pre validated questionnaire.Results: The mean age of the study population was found to be 14.91 (+ 1.45) years. Teaching intervention improves knowledge on reproductive and sexual health (p < 0.001). Predictors of poor pre intervention knowledge levels: those with uneducated fathers (OR= 0.31, p=0.005); not on social networking sites (OR= 0.23, p<0.001); lower age (early adolescence) (OR= 2.46, p<0.001); school going adolescents (OR= 3.47, p<0.001)Conclusion: This study highlights the gross lacunae present among adolescent girls with respect to reproductive and sexual health awareness. Various measures must be put into place to ensure better reproductive health of the adolescent.